Comparison of dynamic methods of road pavement evenness evaluation - Martin Decky (Communications - Scientific letters of the University of Zilina, 1999)
The paper presents the review of dynamic methods of road pavement evenness evaluation used in the Slovak Republic. The principles of assessment by parameters C and IRI (International Roughness Index) are detailed here. The measuring set called the Single-Wheel Vehicle of the University of Žilina (JP VŠDS), which appreciates parameter C has been designed on the DMS (double-mass measuring set) dynamic principle. The design of this system pavement assessment in term of longitudinal unevenness was realised for a consideration stationary random process. The conclusion of our paper is devoted to the comparison of longitudinal unevenness evaluated by our equipment, measuring vehicle „Profilograph“ (IRI) and original parameter IRI.